Developing an Environmentally Sustainable Business Plan: An International B2B Case Study. (10th April 2017) - Gabler, Colin B.; Panagopoulos, Nikolaos; Vlachos, Pavlos A.; Rapp, Adam
Abstract: Business may be in the best position to address the world's environmental problems. However, firms are still struggling with the how and when of their sustainability strategies. The goal of this case study is to uncover bridges and barriers to incorporating environmental issues into business strategy. We collect semi‐structured depth interviews with upper level executives at a global, B2B manufacturing firm. Analysis reveals six elements of an environmentally sustainable business plan: (1) unify the organizational vision, (2) create visible leadership, (3) address multiple stakeholders, (4) focus on innovation, (5) communicate the message, and (6) implement the strategy. We nest these components under the normative, strategic, and operational management framework of corporate sustainability, and then present future research directions. Copyright © 2017 John Wiley & Sons, Ltd and ERP Environment